Human Rights in Employment:: Implications of the International Consensus for Management Teaching and Practice - Adams, Roy (Journal of Comparative International Management, 2001)
The term human rights in employment is commonly used to refer to the rights of minorities to be treated fairly and with justice. The term, however, rightfully encompasses a broader range of issues. There is in fact a very strong international consensus that, in addition to protection against discrimination in employment, young children should not be permitted to engage in exploitative forms of work and employees everywhere should enjoy freedom from forced labour, freedom of association, and the right to bargain collectively. Action designed to thwart the enjoyment of these standards are human rights violations. The term "human rights violation" most often comes up in the context of discussions about conditions in some of the world's poorer nations but the rights of workers in the supposedly advanced countries are far from sacrosanct. Although it attracts little adverse attention, the North American employment practice of union avoidance sabotages the right to bargain collectively and thus is morally wrong. It should not be practised by business and it should not be taught in business schools. From a human rights perspective the practice of union avoidance is the moral equivalent of forced labour, child labour and overt discrimination. If you are sceptical, I can understand. When this notion first occurred to me my reaction was to reject it. Over the years, however, I became a convert to the extent that in 1997 I helped found an organization dedicated to promoting awareness and compliance with core labour rights as human rights. Let me review with you the tortuous road that I travelled to get to this point.